Efektifitas Acuyoga terhadap Keluhan Insomnia pada Ibu hamil Trimester III di Masyarakat Agriculture Traditional di Wilayah Kerja Puskesmas Ngancar Kabupaten Kediri - Nevy Norma Renityas; Levi Tina Sari; Wahyu Wibisono (STIKes Patria Husada Blitar, 2017)
Pregnant mother in the 3rd trimester usually experience sleep disorder caused by dis- comfort of pain on waist due to the enlargement of uterus to the anterior position.The decline of sleep duration of pregnant mother can also make their condition and concentration decreased, experience fatigue, body feels stiff, mood swing, and tend to be emotional. This condition makes the pregnancy becomes more severe than before (Bambang BR, 2004). Therefore, acuyoga technique is applied in order toreduce insomnia. Acuyoga consists of breathing exercises, meditation, relax- ation, and using meridian points in the body to cope with stress and back pain that can cause insomnia in pregnant women. The purpose of this study was to determine the effectiveness of acuyoga techniques to insomnia complaints of 3rd trimester of pregnant women in traditional agricultural communities. The research method used pretest-posttest design with consecutive sampling tech- nique and the number of samples was 40 mothers divided into 4 groups, each group was given treatment 4times in 2 weeks. The measuring tool used the questionnaire and the ISI scale then ana- lyzed by paired sample t-test. The results of the study showed there were an effect of acuyoga tech- nique to insomnia in pregnant women with t count = 13.397 with ttable = 0.021. It was expected that acuyoga technique could be one of the techniques to reduce insomnia in pregnant women since it could relax the muscles in the body so that pregnant women felt comfortable.